Pengaruh Online Customer Review dan Influencer Marketing terhadap Purchase Decision dengan Customer Trust sebagai Variabel Mediasi (Studi Kasus pada Konsumen Kuliner di Aplikasi Shopee Food di Kota Semarang) - Saputra, Naufal Rangga; Cahyono, Budhi (ARZUSIN, 2026)
Intense competition in digital food delivery services requires companies to understand the factors that influence consumer purchase decisions, particularly the roles of online customer reviews and influencer marketing, which have shown inconsistent findings in previous studies. This study aimed to analyze the effect of online customer reviews and influencer marketing on purchase decisions, with customer trust as a mediating variable among Shopee Food users in Semarang City. This study used a quantitative approach with an explanatory design, involving 108 Generation Z respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that online customer reviews and influencer marketing had positive and significant effects on customer trust and purchase decisions. In addition, customer trust had a positive effect on purchase decisions and was able to mediate the relationship between online customer reviews and influencer marketing and purchase decisions. The conclusion of this study emphasizes that the management of credible customer reviews and appropriate influencer marketing strategies can increase consumer trust and encourage purchase decisions in Shopee Food services. These findings provide theoretical contributions to the development of studies on digital consumer behavior and practical implications for managing marketing strategies for application-based food delivery services.